MALAGASY ENTREPRENEUR’S PERSPECTIVES: CASE STUDY OF THE BARRIERS OF ENTREPRENEURSHIP IN MADAGASCAR - FENONIAINA, William Mathias Erica (International Journal of Economics, Business, and Entrepreneurship, 2021)
Entrepreneur is the term use to call people who develop their self-career. And it could be due to many reasons. Hence, as digging deeper into the field, many could be the reason that entrepreneurs in developing country faced on. By conducting qualitative research, this study is the result of a deep interview of three entrepreneurs in Madagascar. And such a result, we have found that there are three main reasons as obstacle of entrepreneurial in that country. First is the lack of knowledge, basically depends on the education. Second concerns about government policies, which is often corrupted and out of date, and the last not the least is about the economy of the country itself, which is not stable, so investors are afraid to use their money even though youth have a brilliant idea. Knowing these struggle lead us to know about the proposed solution which are obviously connected to the concerned issues.